2011
DOI: 10.1111/j.1939-1676.2011.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CytokinemRNAExpression in the Bronchoalveolar Lavage Fluid of Horses with Inflammatory Airway Disease and Bronchoalveolar Lavage Mastocytosis or Neutrophilia UsingRESTSoftware Analysis

Abstract: Objectives: The pathophysiology of inflammatory airway disease (IAD) is unknown, but in some cases involves the accumulation of mast cells, neutrophils, or both in the bronchoalveolar lavage fluid (BALF). The objective of this study was to characterize cytokine gene expression in the BALF cells of horses with IAD, including a comparison of cytokine gene expression between IAD horses with increased BALF mast cells (IAD-Mast) or neutrophils (IAD-Neutro).Methods: The mRNA expression of IL-4, IFN-c, IL-17, IL-8, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 39 publications
(53 reference statements)
6
67
2
Order By: Relevance
“…Similar results have been found for IAD [51, 52] and human asthma and COPD [53, 54]. In our study, the highest concentrations were found in CIP, where IL-1ß is known to stimulate the fibronectin and collagen synthesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results have been found for IAD [51, 52] and human asthma and COPD [53, 54]. In our study, the highest concentrations were found in CIP, where IL-1ß is known to stimulate the fibronectin and collagen synthesis.…”
Section: Discussionsupporting
confidence: 91%
“…Former studies have led to contrasting results. While some authors found no significant increases in IL-6 were found in RAO exacerbation [50, 55, 56], others describe increases about three days after natural challenge [48, 52]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mRNA expression of IL‐17 and IL‐23 have been also linked with increases in BALF neutrophil percentage,54, 59 and increases in IL‐4 and IL‐5 with the mastocytic form of IAD,27, 54 which would support an implication of the adaptive immune response, including Th‐2 type polarization, in some IAD phenotypes.…”
Section: Pathogenesismentioning
confidence: 82%
“…The presence of high eosinophil or mast cell counts, and of Th‐2 cytokines such as IL‐4 and IL‐5, in BALF of some horses with IAD suggest a role for aeroallergens in this syndrome 27, 54. Indeed, exposure to airborne particles has been linked to BALF eosinophilia49 and tracheal mucus51 in young racehorses in training.…”
Section: Pathogenesismentioning
confidence: 99%
“…However, in young horses, numbers of mast cells and eosinophils in BALF are often increased, suggesting hypersensitivity 1, 3, 4, 5, 6, 7. Different cytologic manifestations of equine asthma might reflect differing disease mechanisms with different implications for performance.…”
Section: Introductionmentioning
confidence: 99%